Grammaticalisation of conditional constructions in Portuguese: courses of change regarding the noun caso - Longhin, Sanderleia Roberta [UNESP] (Univ Santiago Compostela, 2020)
The purpose of this paper is to research the historical change processes leading to conditional constructions with caso in the history of Portuguese. Taking into account the theoretical frame of grammaticalization (Heine & Kuteva 2007; Bybee 2010, 2015), together with translinguistic trends in the emergence of conditionals (Traugott 1985; Kortmann 1997), the aim is to find diachronic support to provide answers to the when and how for these changes. This analysis is based on data extracted from a longitudinal sample comprising texts from various genres, written between the 14th and 20th century. The research centres on the analysis of properties of the source nominal item which have enabled the development of different functional patterns of caso, in the domain of conditional junction. The argument presented herein is that the noun caso belongs to a particular subset of generic and unspecific shell nouns (Schmid 2000) whose semantic-cognitive and textual properties explain its choice for conditional expression in different patterns. The research results obtained by joining qualitative and quantitative approaches provide a set of evidence about change-conditioning contexts, about likely derivation relationships among the patterns of caso and about the gradience in the constitution of forms and meanings.
Keywords: Grammaticalization; conjunction; Brazilian Portuguese; conditionality